2016
DOI: 10.3390/molecules22010035
|View full text |Cite
|
Sign up to set email alerts
|

Serum Interleukin-34 Levels Are Elevated in Patients with Systemic Lupus Erythematosus

Abstract: Interleukin-34 (IL-34) was initially identified as an alternative ligand for the colony-stimulating factor-1 receptor (CSF-1R) to mediate the biology of mononuclear phagocytic cells. Recently, IL-34 was found to be associated with chronic inflammation, such as in rheumatoid arthritis (RA). Both RA and systemic lupus erythematosus (SLE) are multifactorial autoimmune diseases and are characterized by excessive immune and inflammatory responses. Thus, we investigated whether IL-34 is involved in the pathogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 22 publications
6
36
0
Order By: Relevance
“…In contrast to M-CSF, IL-34 is undetectable in the serum of healthy subjects [23]. An overexpression of IL-34 has been reported in some severe diseases associated with chronic inflammation, such as viral infections [37,77], inflammatory bowel diseases [78], rheumatoid arthritis [76,79], systemic lupus erythematosus [80], and Sjogren's syndrome [81]. In contrast, one study has reported a decrease in IL-34 expression in patients chronically infected by hepatitis B virus [82].…”
Section: Il-34 In Inflammatory Disordersmentioning
confidence: 99%
“…In contrast to M-CSF, IL-34 is undetectable in the serum of healthy subjects [23]. An overexpression of IL-34 has been reported in some severe diseases associated with chronic inflammation, such as viral infections [37,77], inflammatory bowel diseases [78], rheumatoid arthritis [76,79], systemic lupus erythematosus [80], and Sjogren's syndrome [81]. In contrast, one study has reported a decrease in IL-34 expression in patients chronically infected by hepatitis B virus [82].…”
Section: Il-34 In Inflammatory Disordersmentioning
confidence: 99%
“…Importantly, IL‐34 is induced at protein level under inflammatory conditions including autoimmune diseases. Indeed, several studies have shown that serum IL‐34 levels are increased in rheumatoid arthritis and systemic lupus erythematosus . Furthermore, recent studies have demonstrated that IL‐34 promotes the differentiation of monocytes into profibrotic macrophages .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies have shown that serum IL-34 levels are increased in rheumatoid arthritis and systemic lupus erythematosus. 5,6 Furthermore, recent studies have demonstrated that IL-34 promotes the differentiation of monocytes into profibrotic macrophages. 7 Consistent with this, serum IL-34 levels correlate with the severity of liver fibrosis in patients with chronic hepatitis C, where macrophages acquire profibrotic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies concerning IL‐34 in connective tissue diseases (CTDs) have been reported. It has been shown that serum IL‐34 levels were elevated in patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), as well as systemic sclerosis (SSc), and were associated with disease activity to varying degrees . As a member of the CTDs, pSS was also revealed to be associated with IL‐34, and it was shown that IL‐34 messenger RNA (mRNA) was significantly up‐regulated in the inflamed salivary glands of patients with pSS and associated with local expansion of pro‐inflammatory CD14 bright CD16 + monocytes .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that serum IL-34 levels were elevated in patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), as well as systemic sclerosis (SSc), and were associated with disease activity to varying degrees. [12][13][14][15][16] As a member of the CTDs, pSS was also revealed to be associated with IL-34, and it was shown that IL-34 messenger RNA (mRNA) was significantly up-regulated in the inflamed salivary glands of patients with pSS and associated with local expansion of pro-inflammatory CD14 bright CD16 + monocytes. 10 However, the role of IL-34 in the peripheral blood of patients with pSS and how it might correlate with clinical parameters are still unknown.…”
mentioning
confidence: 99%